2011
DOI: 10.1124/jpet.111.179994
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Level of Ecto-NTP Diphosphohydrolase1/CD39 Modulates Exocytotic and Ischemic Release of Neurotransmitters in a Cellular Model of Sympathetic Neurons

Abstract: Once released, norepinephrine is removed from cardiac synapses via reuptake into sympathetic nerves, whereas transmitter ATP is catabolized by ecto-NTP diphosphohydrolase 1 (ENTPDase1)/CD39, an ecto-ATPase. Because ATP is known to modulate neurotransmitter release at prejunctional sites, we questioned whether this action may be ultimately controlled by the expression of E-NTPDase1/CD39 at sympathetic nerve terminals. Accordingly, we silenced E-NTPDase1/CD39 expression in nerve growth factor-differentiated PC12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Conversely, over-expression of E-NTPDase 1/CD39 resulted in enhanced removal of exogenous ATP [618] and protection against murine myocardial ischaemic injury [619]. Since ATP availability greatly increases in myocardial ischaemia, it has been suggested that recombinant E-NTPDase 1/CD39 may offer a novel therapeutic approach to the damage caused by ischaemia by reducing sympathetic activity [618]. E-NTPDase 1/CD39 deletion led to an attenuation of the activity of sympathetic pre-and post-synaptic P2XR (attributed to P2XR desensitisation) perhaps due to prolonged exposure to ATP that accompanies E-NTPDase 1/CD39 deletion, and it was suggested that E-NTPDase 1/CD39 can potentially prevent the transition from myocardial ischaemia to infarction [620].…”
Section: Ischaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, over-expression of E-NTPDase 1/CD39 resulted in enhanced removal of exogenous ATP [618] and protection against murine myocardial ischaemic injury [619]. Since ATP availability greatly increases in myocardial ischaemia, it has been suggested that recombinant E-NTPDase 1/CD39 may offer a novel therapeutic approach to the damage caused by ischaemia by reducing sympathetic activity [618]. E-NTPDase 1/CD39 deletion led to an attenuation of the activity of sympathetic pre-and post-synaptic P2XR (attributed to P2XR desensitisation) perhaps due to prolonged exposure to ATP that accompanies E-NTPDase 1/CD39 deletion, and it was suggested that E-NTPDase 1/CD39 can potentially prevent the transition from myocardial ischaemia to infarction [620].…”
Section: Ischaemiamentioning
confidence: 99%
“…Ecto-nucleotidase on sympathetic nerve endings attenuates ATP and NA exocytosis in myocardial ischaemia by reducing ATP levels and consequently the prejunctional facilitatory effects of ATP [580]. Conversely, over-expression of E-NTPDase 1/CD39 resulted in enhanced removal of exogenous ATP [618] and protection against murine myocardial ischaemic injury [619]. Since ATP availability greatly increases in myocardial ischaemia, it has been suggested that recombinant E-NTPDase 1/CD39 may offer a novel therapeutic approach to the damage caused by ischaemia by reducing sympathetic activity [618].…”
Section: Ischaemiamentioning
confidence: 99%
“…Ectonucleotidase on sympathetic nerve endings attenuates ATP and NA exocytosis in myocardial ischemia (by reducing ATP levels and consequently the prejunctional facilitatory effects of ATP) (Sesti et al, 2003). Conversely, overexpression of E-NTPDase 1/CD39 resulted in enhanced removal of exogenous ATP (Corti et al, 2011) and protection against murine myocardial ischemic injury (Cai et al, 2011). Because ATP availability greatly increases in myocardial ischemia, it has been suggested that recombinant E-NTPDase 1/CD39 may offer a novel therapeutic approach to the damage caused by ischemia by reducing sympathetic activity (Corti et al, 2011).…”
Section: Ischemiamentioning
confidence: 99%
“…Conversely, overexpression of E-NTPDase 1/CD39 resulted in enhanced removal of exogenous ATP (Corti et al, 2011) and protection against murine myocardial ischemic injury (Cai et al, 2011). Because ATP availability greatly increases in myocardial ischemia, it has been suggested that recombinant E-NTPDase 1/CD39 may offer a novel therapeutic approach to the damage caused by ischemia by reducing sympathetic activity (Corti et al, 2011). E-NTPDase 1/CD39 deletion led to an attenuation of the activity of sympathetic pre-and postsynaptic P2X receptors (attributed to P2X receptor desensitization) perhaps because of prolonged exposure to ATP that accompanies E-NTPDase 1/CD39 deletion, and it was suggested that E-NTPDase 1/CD39 can potentially prevent the transition from myocardial ischemia to infarction (Schaefer et al, 2007).…”
Section: Ischemiamentioning
confidence: 99%
“…at ASPET Journals on May 9, 2018 jpet.aspetjournals.org ron (Morrey et al, 2008;Corti et al, 2011). We found that Alda-1 (100 M; 20 min) elicited a Ն60% increase in ALDH2 activity (Fig.…”
Section: Aldh2 Inhibits Ne Release In Ischemic Heart Neurons 101mentioning
confidence: 75%